Mapping the landscape of computer-assisted language learning: an inventory of research - Zaphiris, Panayiotis; Ioannou, Andri; Papadima-Sophocleous, Salomi; Parmaxi, Antigoni (My University, 2013)
Purpose – The purpose of this study is to chart the development in computer-assisted language learning (CALL), by building a map of existing research work in the field. Based on a corpus of 163 manuscripts, published between January 2009 and September 2010 in four major journals devoted to CALL, it sets out to describe the range of topics covered under the umbrella of CALL and provide a holistic view of the field. Design/methodology/approach – The approach adopted in this research includes: development of the 2009-2010 CALL corpus; literature overview and initial coding scheme development; refinement of the initial coding scheme with the help of a focus group and construction of the CALL map version 1.0; refinement of the CALL map version 1.0 following a systematic approach of content analysis and development of the CALL map version 2.0; evaluation of the proposed structure and inclusiveness of all categories in the CALL map version 2.0 using card sorting technique; and finally development of the CALL map version 3.0. Findings – The research trends in the categories of the CALL map are discussed, as well as possible future directions in the field. Originality/value – This paper provides a holistic view of the field of CALL guiding both junior CALL researchers to place themselves in the field, and policy and decision makers who attempt to evaluate the current and future scholar activity in the field. Finally, it caters for more experienced researchers to focus on certain underinvestigated domains.
Keywords: Communication technologies; E-learning